Desigualdades regionais na política educacional: o caso do salário-educação - Cerqueira, Leandro de Borja Reis (2018)
The objective of this study is to analyze the Salary-Education, social contribution intended for funding actions of basic public education, aiming to identify whether it contributes to reduce inequalities among entities of the federation, in relation to offer of education. The conducted research may be characterized as exploratory, having as methodological basis the bibliographic and documental research. The bibliographic research featured the study of classic and contemporary works of Education and Social Sciences, besides scientific papers, dissertations and theses that address the proposed thematic. Through documentary research, laws and regulations regarding to the subject were analyzed. In addition, quantitative and qualitative analysis of statistical data was done. In order to answer the research problem stablished, the investigations were based on the observation of the complex interdependency characteristics among the educational systems for compliance with constitutional arrangements related to the assurance of the right of education; looked for evaluate the balance between the attributed competences to the federative entities by the legislation and available resources sought to evaluate the balance between the competences attributed to federative entities by the legislation and the resources available for it; in addition to examining the distribution of the salary-education resources among the federative units.